2016
DOI: 10.1098/rstb.2015.0133
|View full text |Cite
|
Sign up to set email alerts
|

A molecular palaeobiological exploration of arthropod terrestrialization

Abstract: Understanding animal terrestrialization, the process through which animals colonized the land, is crucial to clarify extant biodiversity and biological adaptation. Arthropoda (insects, spiders, centipedes and their allies) represent the largest majority of terrestrial biodiversity. Here we implemented a molecular palaeobiological approach, merging molecular and fossil evidence, to elucidate the deepest history of the terrestrial arthropods. We focused on the three independent, Palaeozoic arthropod terrestriali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
124
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 107 publications
(212 reference statements)
10
124
1
1
Order By: Relevance
“…Spiders evolved from an arachnid ancestor in the late Ordovician around 450 million years ago and they are now the most speciose invertebrates on the planet after insects and mites. About ∼48 000 species have been morphologically characterized and assigned taxonomic names, but this likely represents less than a third of all living spider species; indeed, the total number of extant species might exceed the total number of venomous animals in all other terrestrial phyla .…”
Section: Spiders Are Professional Insect Killersmentioning
confidence: 99%
“…Spiders evolved from an arachnid ancestor in the late Ordovician around 450 million years ago and they are now the most speciose invertebrates on the planet after insects and mites. About ∼48 000 species have been morphologically characterized and assigned taxonomic names, but this likely represents less than a third of all living spider species; indeed, the total number of extant species might exceed the total number of venomous animals in all other terrestrial phyla .…”
Section: Spiders Are Professional Insect Killersmentioning
confidence: 99%
“…Diversification of Dignatha is inferred to date to the latest Cambrian-Early Ordovician, Progoneata to the mid-late Cambrian, and Myriapoda to the early-middle Cambrian (auto- and uncorrelated rates, respectively). The shared terrestrial adaptations of all extant myriapods (e.g., tracheae, Malpighian tubules, uniramous trunk limbs) suggest that the common ancestor of each of these estimated Cambrian nodes was terrestrial, coinciding (although being slightly younger) with estimates of terrestrialisation for other arthropod lineages, including arachnids and hexapods [3, 5]. Although the trace fossil record is consistent with amphibious arthropods by the mid Cambrian [21, 22], these molecular estimates for early or middle Cambrian crown-group myriapods continue to pose an unanswered question in arthropod terrestrialisation.…”
Section: Resultsmentioning
confidence: 99%
“…The age of the duplication event identified here must predate the most recent common ancestor of spiders and scorpions. Molecular clock approaches vary widely on the age of arachnids, and have suggested that arachnids diversified in the Ordovician (Lozano-Fernandez et al, 2016;Rota-Stabelli et al, 2013) or in the Silurian (Sharma and Wheeler, 2014), with large confidence intervals on node age estimates that often span entire geological periods. However, the earliest stem-group spiders (the extinct order Uraraneida) date to the mid-Devonian (386 MYA; Selden et al (2008)), whereas discoveries of Paleozoic scorpions have extended the stratigraphic range of scorpions into the Silurian (430 MYA; Waddington et al (2015)).…”
Section: Gene Duplication and Arachnid Evolutionmentioning
confidence: 99%